Pemasaran Desain Produk Prespektif Hukum Ekonomi Syariah - Atabik, Ahmad (TAWAZUN: Journal of Sharia Economic Law, 2018)
Marketing strategy is a statement (both implicit and explicit) about how a brand or product line reaches its goal. Meanwhile, Tull and Kahle (1990) defined a fundamental tool strategy planned to achieve company goals by developing sustainable competitive advantages through the market entered and marketing programs used to serve the target market. In each step, marketing activities and activities must always be based on Islamic shari'a. Sharia marketing believes that these divine laws are the most ideal, the most perfect, most appropriate for all forms of goodness and most can prevent all forms of damage. A Shari'ah marketer even though he is not able to see God, he will always feel that God is always watching him. So that he will be able to avoid all kinds of actions that cause other people to be deceived.